A crazy day with cobras ebook - Osborne, Mary Pope (Magic Tree House: Merlin Missions, 2011)
The #1 bestselling chapter book series of all time celebrates 25 years with new covers and a new, easy-to-use numbering system! Merlin’s beloved penguin, Penny, has been put under a spell! To save her, Jack and Annie must find a rare and precious emerald. When the magic tree house whisks them back to India over four hundred years ago to search for the jewel, they discover an amazing and exotic world filled with great danger. Formerly numbered as Magic Tree House #45, the title of this book is now Magic Tree House Merlin Mission #17:  A Crazy Day with Cobras . Did you know that there’s a Magic Tree House book for every kid? Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Super Edition: A longer and more dangerous adventure Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures Have more fun with Jack and Annie at MagicTreeHouse.com!